2004
DOI: 10.3171/spi.2004.1.2.0175
|View full text |Cite
|
Sign up to set email alerts
|

Does chronic cervical myelopathy affect respiratory function?

Abstract: Object. Although respiratory function is often impaired by acute cervical spinal cord injury, changes in respiratory function in patients with chronic cervical myelopathy (CCM) are not well documented. The purpose of this study was to evaluate the respiratory function of patients with CCM. Methods. Spirometric parameters were measured in 94 patients with CCM before they underwent e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 14 publications
3
38
0
Order By: Relevance
“…The study also showed that although there was a significant improvement in the FVC values, the improvement did not equal the control values. The results were commensurate to the earlier studies by Toyoda et al 17 and Ishibe and Takahashi, 9 in which they reported lower values for % vital capacity (%VC), %FVC, PEFR, and increased respiratory rate and expiratory velocities at 50% and 25% of vital capacity. Yanaka et al 18 re- ported low tidal volumes that showed significant improvement after surgery.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The study also showed that although there was a significant improvement in the FVC values, the improvement did not equal the control values. The results were commensurate to the earlier studies by Toyoda et al 17 and Ishibe and Takahashi, 9 in which they reported lower values for % vital capacity (%VC), %FVC, PEFR, and increased respiratory rate and expiratory velocities at 50% and 25% of vital capacity. Yanaka et al 18 re- ported low tidal volumes that showed significant improvement after surgery.…”
Section: Discussionsupporting
confidence: 81%
“…13,17 The studies considered in this review suggest that the abnormality is subclinical, can involve inspiratory or expiratory flow differently, and can be complete or incomplete.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…In a small cohort of CSM patients, however, Yanaka et al, 22 who demonstrated a postoperative increase of tidal volume with a reduction of PCO 2 , failed to find such a favorable effect of surgery on %VC. Also as for %VC, Toyoda et al 5 reported that the CCM group showed significantly lower values than the control group with a further decrease for the CCM group with a higher lesion level of C3-4. All these studies, however, did not test MVV, which might be able to assess the subclinical impairment of ventilatory muscle coordination.…”
Section: Discussionmentioning
confidence: 99%
“…The ventilatory function in CSM, however, has not been investigated as extensively as that in cervical spinal cord injury (SCI); [1][2][3] only a few studies 4,5 have attempted to demonstrate a difference in routine spirometric data and flow volume curves between chronic-onset cervical myelopathies with various etiologies and control groups with lumbar lesions. However, those studies did not use the maximum voluntary ventilation (MVV) test, which, in one study, 6 has been shown to be more sensitive than vital capacity (VC) and forced expiratory volume in 1 s (FEV 1 ) to the improved respiratory endurance after a form of respiratory muscle training in athletes.…”
Section: Introductionmentioning
confidence: 99%